My Best Friend Is Invisible - Stine, R L (New York Scholastic, 1997)
Sammy Jacobs is very interested in ghosts and science fiction much to the dismay of his parents who are research scientists, but when he somehow acquires an invisible friend, he realizes that the supernatural is not all that much fun
Keywords: Children's Literature - Fiction : Horror